Protection Model For Minors As Witnesses And Victims Of Sexual Violence: A Local Wisdom Approach From The Buton Archipelago Community - Mansyah, Muh Sutri; La Ode Fajrul Islam Sabti,; Yetty Purnamasari,; Subhan Alfajar, (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
Sexual violence is a serious crime requiring multidimensional handling, making this research highly urgent due to the absence of prior studies specifically analyzing a local wisdom-based child protection model in the region. The findings reveal differences and similarities in the child protection models across the three districts. In Central Buton, perpetrators face customary and social sanctions, including partial body burial or a pocong oath (swearing while wrapped in a shroud) if they refuse to admit their actions. In South Buton, offenders are required to pay boka (customary fines). Meanwhile, in Buton District, perpetrators are exiled from the village, subjected to customary fines, and undergo the Kaleoleo ritual submerging their head in the sea; if dishonest, they cannot endure long underwater. All three customary institutions share similarities in their decision-making process for imposing sanctions through council deliberations involving the Mosque Imam, Sara, Parabela, Village Head, and Neighborhood Chief. It is recommended to revise regulations both at the legislative and regional levels to ensure effective implementation.